2021
DOI: 10.3390/app11020660
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment of a Gasification Plant for Distributed Cogeneration in the Agrifood Sector

Abstract: This research work presents a techno-economic analysis of a biomass gasification plant fueled with residues from the olive oil and almond industries for combined heat and power generation in the agrifood sector. The experimental plant consists of a downdraft fixed bed gasifier, a producer gas cleaning and cooling system and a spark-ignition engine–generator set as a power generation unit, which generates about 10–12 kW of rated electric power. With an average consumption between 13–14 kg/h of exhausted olive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…When kiln's capacity increases from 20,000 to 100,000 bricks per batch, PBP reduces from 7.93 to 4.02 years. Aguado et al (2021) also reported a similar trend of PBP in the implementation of gasifier in agricultural food processing sector. Normally, the increase in capacity or size of a renewable energy system reduces the rate of capital and running costs (Beno and Edwin 2020; Glivin et al 2018), which is also seen in Figs.…”
Section: Resultssupporting
confidence: 55%
“…When kiln's capacity increases from 20,000 to 100,000 bricks per batch, PBP reduces from 7.93 to 4.02 years. Aguado et al (2021) also reported a similar trend of PBP in the implementation of gasifier in agricultural food processing sector. Normally, the increase in capacity or size of a renewable energy system reduces the rate of capital and running costs (Beno and Edwin 2020; Glivin et al 2018), which is also seen in Figs.…”
Section: Resultssupporting
confidence: 55%
“…Gasification plants can be installed at the olive oil mills in self-consumption mode, in order to reduce the electricity costs. This solution require regular maintenance, then enabling "the creation of a permanent part-time technical job" [53]. Presenting a high content of carbon and hydrogen, and conversely a low level of ash and moisture, with a considerable heating value, exhausted olive pomace is considered to be the most appropriate olive oil by-product for feeding the gasifier plants [53], also thanks to its massive production rate and thus high-volume availability.…”
Section: Biofuel Production From Pruning Residues And/or Olive Mill Wastes or Waste Cooking Oilmentioning
confidence: 99%
“…This solution require regular maintenance, then enabling "the creation of a permanent part-time technical job" [53]. Presenting a high content of carbon and hydrogen, and conversely a low level of ash and moisture, with a considerable heating value, exhausted olive pomace is considered to be the most appropriate olive oil by-product for feeding the gasifier plants [53], also thanks to its massive production rate and thus high-volume availability. However, due to the small size of olive pomace's raw particles, pelletizing it in advance is preferable to a direct use (ibidem).…”
Section: Biofuel Production From Pruning Residues And/or Olive Mill Wastes or Waste Cooking Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Weather conditions not only affect electricity production from both solar and wind but also directly impact electricity demand [1]. The highest demand is observed in the summer and the lowest demand usually occurs in the spring [2]. Similarly, demand varies across the day; it is higher during working hours, i.e., from morning until evening [3,4].…”
Section: Introductionmentioning
confidence: 99%